Modular stormwater blocks. - Ghazali, Abdul Halim (2006)

(untitled)
The Putra Stormwater Block (PSB) has been invented for use primarily in the stormwater management. Its components are the holders and the pipes, both are made of rigid Polyvinylchloride (PVC-U) material. The holders require special fabrication but the pipes can be readily obtained from the market. The blocks can be used in modular form to suit any area and depth requirement. The block allows water to pass through easily, both in vertical and horizontal directions. It also has high percentage of void that allows it to store water. The weight and dimensions of the blocks allow them to be easily placed by manual labours.The PSB is suitable for use below a parking area as it has high strength that can withstand the normal traffic loadings. When used with appropriate porous paving materials, surface water can enter the blocks through the pavers and it will then be stored within the blocks. With proper connection drainage system, the water can be released slowly from the storage, preventing the drainage from receiving too much flow each time it rains. The stored water can also infiltrate into the underlying soil if a proper bedding layer is provided below the blocks. Thus, the blocks will help to reduce the occurrence of surface ponding and drainage overflows, as well as to recharge the groundwater.